(3LGeY GdcfhR hfaGFS GdJbQjQ aj TQM GdhdOjI ef BOGH GdefGXQIs - (3GdJHQjRj, GdeQYTj GdQhej, GdMfaj, MSjf Hf MjOQ (B, (3cGf MjG (B1176 (3g`s ((3UGdM Hf ESeGYjds)
(3ChdgG (B:s
(3GdMeO ddg GdPj NjQ YHGOg SHjd GdUhGH deG cGfJ GdQSGdI GdhdOjI aj Yde GdBOGH eTghQI hebHhdI Hjf Ghdj GdCdHGH HMjK fXeJ aj Sdc GdePGcQI Hjf GdaMhd hGdWdGH dCSJGPj SGLbdj RGOg (B...s
(3BNQgG (B:s
... (3hef CQGO GdGSJbUGA Cj GdHdhZ Edi GdGfJgGA aj af GdefGXQI aYdjg NHQ ebOe HQSGdJfG eHJOC HRjGOI GdHGA hjMJed Gf jchf GdeYfi aYdjg Cf jfXQ aj QSGdJfG Ch Cf jQLY Edi QSGdJfG GdeYehdI Cj GdeDdaI (B... (3JeJs
(3JHUQI GdeDda (B:s
(3cJH NWC aj ebOeI GdeNWhW (B( (3MSjf Hf MejO (B) (3hGdUhGH GdeKHJ ef GdeUGOQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B1\609s
(3EjVGM Gdecfhf (B1\357s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs